If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(d + 2) = 4(15 + d) Reorder the terms: -9(2 + d) = 4(15 + d) (2 * -9 + d * -9) = 4(15 + d) (-18 + -9d) = 4(15 + d) -18 + -9d = (15 * 4 + d * 4) -18 + -9d = (60 + 4d) Solving -18 + -9d = 60 + 4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4d' to each side of the equation. -18 + -9d + -4d = 60 + 4d + -4d Combine like terms: -9d + -4d = -13d -18 + -13d = 60 + 4d + -4d Combine like terms: 4d + -4d = 0 -18 + -13d = 60 + 0 -18 + -13d = 60 Add '18' to each side of the equation. -18 + 18 + -13d = 60 + 18 Combine like terms: -18 + 18 = 0 0 + -13d = 60 + 18 -13d = 60 + 18 Combine like terms: 60 + 18 = 78 -13d = 78 Divide each side by '-13'. d = -6 Simplifying d = -6
| 90+x=125 | | -2(16-3p)=-5p+1 | | 2-y=1 | | -50t-5=70 | | 6-9= | | 80+x=95 | | X-0=1 | | -11x-3x=10-10x | | 3(-z+12)=4(z-5) | | 2x-5+3x=5 | | 5-6x=3(1-2x) | | 3n+6=87 | | Z^2-20z-21=0 | | 5y=3(y-2) | | -21=-5v+3(v-5) | | 3b+16=40 | | -16-9-4x=-9 | | =1+1 | | 8x+20=2x+20 | | -5=6n | | 5-3x+2=4x+7 | | 4x^2-23x+13=-7x+6 | | 24-6m=0 | | .5(10z+8)-2=4(z-6) | | 8+9x=-6 | | 2(x+3)=5+2x | | x/3+4=x/6+2 | | 5x+35=7(x+5)-2x | | 6x+3(1+3x)=3+15x | | 3x^6+192=0 | | 2x+24=4(x+6)-2x | | -9-6k+9-(-2k)= |